A Qualitative Analysis of the Motivations for Chinese Gay Tourists Choosing Thailand as a Destination: A Grounded Theory Approach - Kang, Yangyang; Jiang, Songyu (Journal of Ecohumanism, 2024)
Chinese gay tourists, as the largest segment of gay tourists in Thailand, significantly contribute to the development of the Thai pink tourism industry. However, there has been limited research focusing on the motivations of Chinese gay tourists in choosing Thailand as their tourism destination. Utilizing a qualitative approach, this study aims to understand the factors influencing the motivation of Chinese gay tourists in selecting Thailand as their travel destination. Through purposive and snowball sampling, 23 Chinese gays were recruited to participate in semi-structured interviews to gather data. The data were transcribed and analyzed using grounded theory methodology. This study identified six key factors: acceptance and freedom, community and belonging, personal and emotional well-being, accessibility and convenience, sexual freedom and entertainment, and influence of media and friends. These factors collectively influence the motivation of Chinese gay tourists in their choice of tourism destination. Moreover, this study develops a theoretical framework that encapsulates these motivational factors and their interrelations.